ASPEK HUKUM PERLINDUNGAN TENAGA KERJA ASING DI PERUSAHAAN INDONESIA YANG BERADA DALAM KEADAAN PAILIT - YUVINDRI YUVINDRI; RAMLI SIREGAR; WINDHA WINDHA (Universitas Sumatera Utara, 2013)
Companies in Indonesia require skilled labor in certain fields, where the field work cannot be filled by Indonesian workers, so that the companies need foreign labor to cultivate his company. Therefore, the problem in this thesis is how the position of foreign workers in an Indonesian company, how an Indonesian company is said to be in a state of bankruptcy and how the protection of foreign workers in an Indonesian company is declared bankrupt. The method used for this thesis is a normative legal research or library research, by collecting materials from books, legislation, journals and the Internet are closely related to the intent and purposes of the preparation of this manuscript. Position of foreign workers in Indonesia are as labor. Indonesian companies which are in a state of bankruptcy is a company that has two or more creditors and not pay in full at least one debt that has matured and can be billed, declared bankrupt by a court decision, either on its own or upon petition of one or more creditors petition. Protection of foreign workers in Indonesia are bankrupt companies as same as workers in Indonesia, namely the protection of Wages and Termination. Keywords: Perusahaan,Kepailitan,Perlindungan Hukum, Tenaga Kerja Asing